(untitled) (African Multidisciplinary Journal of Research, 2025)
Intercommunal conflict is a challenge to social, economic and political development in Kenya. The Tana Delta region has been experiencing conflicts over the years despite the efforts put in place by various stakeholders in peace building and conflict management among the Pokomo and Orma communities. Hence the need to evaluate the effectiveness of the various approaches employed in conflict management and peace building in the region such as the customary approach, hard power approach, NGOs empowerment model and the community-based approach. This article explores the various strategies employed by stakeholders and peace actors in attaining sustainable peace in Tana Delta, Tana River County, Kenya. The objective of the article is to examine the conflict mitigation strategies used in Tana Delta and assess their effectiveness in peacebuilding and conflict management. It attempts to answer the question, ‘how effective are the tools of conflict management employed in the mitigation of the perennial conflict in Tana Delta region?’ The article uses the Conflict Theory as developed and applied by Dahrendorf (1959) and Bartos and Wehr (2002). It relies on data collected through qualitative research design comprising of In-depth interviews and FGDs conducted on 83 respondents. The article argues that the most sustainable approach in managing intercommunity conflict was the community-based approach through the development of peace committees followed by hard power approach through the deployment of security forces, then the NGOs empowerment model and the customary approach. Sustainable peace is best achieved through an integrated approach that combines traditional, security, and developmental strategies tailored to local contexts. The study concludes that, the success of such approaches depends on contextual factors, community participation, and the integration of cultural practices, all of which are vital for addressing conflicts in areas like the Tana Delta and beyond.